Overall survival and disease-free survival in breast cancer patients treated at the Oncology Centre in Bydgoszcz – analysis of more than six years of follow-up - Nowikiewicz, Tomasz; Wiśniewska, Magdalena; Wiśniewski, Michał; Biedka, Marta; Głowacka, Iwona; Kozak, Dominika; Laskowski, Ryszard; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Malignant breast tumours are the largest oncological problem in the developed world. In the recent years the number of new diagnoses has exceeded 16,500 per year. Published data regarding far-distant results of breast cancer treatment that take under consideration the provincial division of the country may not be representative of the therapeutic effects achieved in specific oncological centres. The goal of this article is to analyse far-distant therapeutic results in breast cancer patients treated at the Oncology Centre in Bydgoszcz in 2006. They were compared with data available for Kujawsko-Pomorskie Voivodeship and with all-Poland results. Material and methods : A cohort of 667 breast cancer patients at Bydgoszcz Oncology Centre between Jan 1 and Dec 31, 2006 was studied. The majority of the studied group were patients in stage I (26.2%) and II (48.3%) according to the TNM staging system, 17.5% were in stage III, and 6.4% in stage IV. The 5-year survival and 5-year disease-free survival rates were calculated. Median observation time was 79 months. Results : A total of 148 patients (22.2%) suffered a relapse. There were 168 (25.2%) deaths caused by primary disease. The 5-year survival probability was 0.761 ±0.017 and the five-year disease-free survival probability was 0.807 ±0.016. Median survival time was 76.4 months, and median disease-free survival was 19.4 months. Conclusions : The five-year survival probability for breast cancer patients undergoing treatment at Bydgoszcz Oncology Centre was higher than all-Poland median five-year survival probability. The observation needs to be continued and should include the assessment of treatment in subsequent time periods.